PENGARUH PENGGUNAAN CHAT GPT SEBAGAI CONTENT CREATION DALAM MEMBANGUN PERSEPSI KONSUMEN TERHADAP STRATEGI PEMASARAN UMKM - Amalia, Syifa; Karomatan, Tresna; Ridwan, Witsqa Inayatussholiha (Jurnal Ilmiah Publika, 2023)
This paper delves into the effects of the society 5.0 period, particularly looking at how AI technology, and Chat GPT in particular, have contributed to societal development. Rapid advancements in artificial intelligence have been made with the release of Chat GPT, the newest breakthrough from Open AI. It can solve a number of hard jobs. Nonetheless, Micro, Small, and Medium Enterprises (MSMEs) become an essential response to the severe lack of employment opportunities and the high level of artificial intelligence (AI), particularly in the context of Chat GPT in Indonesia. Technology, and more specifically Chat GPT as a content production tool, provide problems for micro, small, and medium-sized enterprises (MSMEs) when trying to reach clients online. Chat GPT offers speed and cost efficiency to MSMEs' marketing tactics, but it also raises questions about the future of human work. In light of these dynamics, the question of how society and the government might assist MSMEs in adapting to technological change must be given considerable thought. This study highlights the need of balancing technical innovation with economic sustainability, managing social effect in this age of sophisticated technology, and connecting the use of Chat GPT in content production with MSMEs marketing strategies.